Characterization of Poosti Cheese, a Traditional Raw Sheep Cheese during Ripening: Physicochemical, Microbial and Micro-structural Aspects - Mojgan Hemmatian; Mehrnaz Aminifar; Farnoosh Attar (Nutrition and Food Sciences Research, 2015)
Background and Objectives: This study is the first research on the physiochemical characteristics, microbial population and microstructure of Poosti cheese over 90-days of ripening. The main difference between Poosti cheese and other types of traditional cheese is the skin, which is used for its storage. Materials and Methods: Physicochemical characteristics including moisture, salt, pH, acidity, fat, and rate of water-soluble nitrogen to total nitrogen were measured during the ripening. Total population of mesophilic and psychrotrophic bacteria, Escherichia coli, Coliform, lactic acid bacteria, yeasts and moulds were determined during the aging. Micro-structural properties of Poosti cheese were evaluated by scanning electron microscopy (SEM). Three-dimensional (3D) images, binarised micrographs and surface plot were obtained by analyzing the two-dimensional (2D) SEM micrographs by Image J software. Results: The results showed that the moisture content, pH and fat percentage were decreased during the aging; however, salt, acidity, and ratio of water-soluble nitrogen to total nitrogen were increased during this time. Besides, the total count of bacteria was decreased during the aging. Finally, the SEM images indicated that the density of casein network, the number and depth of pores, and also roughness of the structure were increased during the ripening. Conclusions: According to this study, physicochemical characteristics of Poosti cheese were changed during the aging (salt and fat were increased, while pH and moisture were decreased) as a result of ripening in the skin and high microbial population of raw milk. The microstructure of Poosti cheese was changed during the ripening due to water and salt movement, and the fermentative activity of microbial population. Keywords: Traditional cheese, Physicochemical properties, Microbial properties